Systemic effects of bank equity issues: Competition, stabilization and contagion - Valeriya Dinger; Vlad Marincas; Francesco Vallascas (Osnabrück University, Institute of Empirical Economic Research, 2018)
We evaluate the abnormal returns of issuing and non-issuing banks around the announcement of Seasoned Equity Offerings (SEOs) and explore how the market reaction is influenced by aggregate systemic conditions and by the systemic risk contribution and exposure of banks. While we find evidence of negative abnormal returns for issuers, non-issuing banks benefit from positive abnormal returns around the SEO announcement. We show that these positive returns are not entirely explained by the competition channel, which has been well documented for non-financial firms. In contrast, we demonstrate that they also depend on a so far undocumented system-stabilizing channel. Furthermore, under certain circumstances, the system-stabilizing channel contributes to mitigating the negative reaction to SEO announcements for the issuing banks.
Keywords: G21; G28; G32; 330; SEOs; Banking Regulation; Banking Crises; Contagion; Systemic Risk